Territorialidades da educação do campo na região sudoeste do Paraná na última década (2000-2010) - Pereira, Amarildo Nunes (2013)
The National Movement By a Rural Education arises from the First Meeting of Educators of Agrarian Reform - I ENERA - promoted by MST in July 1997, in Brasilia, this meeting which was held in partnership with the University of Brasilia (UNB), the United Nations Children s Fund (UNICEF), the United Nations Educational, Scientific and Cultural Organization (UNESCO) and the National Conference of Brazilian Bishops (CNBB), representatives of the Catholic Church, Universities, the agencies of the United Nations (UN). In more than a decade, the National Movement for a Rural Education expanded for all Brazil. With the creation of the National Joint, the movement won a series of public policies, with emphasis on the adoption of the operational guidelines in 2002, providing legal support to public policy of the state that values the culture and identity of rural people. The present work has as its theme the Territoriality of Rural Education in the Southwest region of Paraná in the last decade (2000-2010), in order to understand how the Rural Education territorializes itself in rural schools from the popular organizations committed to family farmers. In this sense, the Project Vida na Roça constitutes an example of this process of territorialization of Rural Education in schools of the Southwest of Paraná through partnerships involving the ASSESOAR, among other entities related to the family farm committed to the education of the peasants. It was possible to understand how public policies are territorialized in empirical research, conducted at Iraci Salete Strozak and São Francisco do Bandeira Rural Schools. The systematized answers pointed three modes used by teachers to set a rural school: differentiated methodology, curriculum common basis, theory and practice. Research has shown that the rural school is a contradictory territory, where the class struggle is manifested itself in the disputes by education projects and field. The Rural Education is much more than school, it is a political movement bound to the social movements for structural change of society and the state.